Contours of India - Nepal Relationship and Trans-Boundary Rivers Water Disputes - Ranjan, Amit (Journal of International Affairs, 2016)
India and Nepal share about 1800 square kilometres of porous border, inhabit the majority of their members from the same religious group and have symbiotic interdependent on each other; yet they are engaged into disputes over many issues. It is always alleged by Nepal that India does not consider it as a sovereign country rather as one of its own administrative unit. The basis of this allegation is behaviour of Indian establishment and its epistemic community towards Nepal. The political tensions between the two countries have kept on surfacing at intermittent period and have influenced the water sharing arrangements between the two countries. Nepal alleges that as a powerful country, India exploits Nepal’s natural resources for its own benefit. As a result many of the transboundary river water treaties have not been activated, some have been sternly opposed by the people from the catchment areas, and a few’s future is hanging in the air. To overcome these problems and its dependency on India, many times Nepal has invited other countries to develop its hydropower sector. Amidst all existing differences the two countries share inextricable relationship because of geographical location and shared primordial identity.